To calculate the value of the expression 3 x 10^11 - 3 x 10^12, we can first simplify it by factoring out a common factor of 3 x 10^11 from both terms:
3 x 10^11 - 3 x 10^12 = (3 x 10^11) x (1 - 10)
Next, we can simplify the expression inside the parentheses:
1 - 10 = -9
Now, we can substitute this value back into the equation:
3 x 10^11 - 3 x 10^12 = (3 x 10^11) x (-9)
Finally, we can calculate the product of (-9) and (3 x 10^11):
(3 x 10^11) x (-9) = -27 x 10^11
Therefore, 3 x 10^11 - 3 x 10^12 simplifies to -27 x 10^11.
3 x 10^11 - 3 x 10^12
1 answer